# How do you evaluate 5^2*(-3)-4*6+7?

Sep 16, 2016

$- 92$

#### Explanation:

We have: ${5}^{2} \cdot \left(- 3\right) - 4 \cdot 6 + 7$

Let's use the rules of operator precedence, "PEMDAS":

$= 25 \cdot \left(- 3\right) - 4 \cdot 6 + 7$

$= - 75 - 4 \cdot 6 + 7$

$= - 75 - 24 + 7$

$= - 99 + 7$

$= - 92$

Sep 16, 2016

$- 92$

#### Explanation:

In any expression with different operations, it is important to COUNT terms first. Each term will simplify to a single answer.

Within each term the order of operations is applied:
Brackets
Powers and roots
multiply and divide

You can work in different terms in the same line.

Once there is a single answer to each term, these are added or subtracted in the last step, working from left to right.

$\textcolor{red}{{5}^{2}} \times \left(- 3\right) \textcolor{b l u e}{- 4 \times 6} \textcolor{\lim e}{+ 7} \text{ } \leftarrow$ there are 3 terms

=color(red)(25xx(-3) color(blue)(-24)color(lime)(+7)

=$\textcolor{red}{- 75} \textcolor{b l u e}{- 24} \textcolor{\lim e}{+ 7}$

It is often easier to re-arrange the terms with the plus terms at the beginning and the minus terms at the end.

=$\textcolor{\lim e}{+ 7} \textcolor{red}{- 75} \textcolor{b l u e}{- 24}$

=$- 92$